Genome-Wide Analysis of the Stationary-Phase Sigma Factor (Sigma-H) Regulon of Bacillus subtilis - Britton, Robert A. (American Society for Microbiology, 2002)
Sigma-H is an alternative RNA polymerase sigma factor that directs the transcription of many genes that function at the transition from exponential growth to stationary phase in Bacillus subtilis. Twenty-three promoters, which drive transcription of 33 genes, are known to be recognized by sigma-H-containing RNA polymerase. To identify additional genes under the control of sigma-H on a genome-wide basis, we carried out transcriptional profiling experiments using a DNA microarray containing >99% of the annotated B. subtilis open reading frames. In addition, we used a bioinformatics-based approach aimed at the identification of promoters recognized by RNA polymerase containing sigma-H. This combination of approaches was successful in confirming most of the previously described sigma-H-controlled genes. In addition, we identified 26 putative promoters that drive expression of 54 genes not previously known to be under the direct control of sigma-H. Based on the known or inferred function of most of these genes, we conclude that, in addition to its previously known roles in sporulation and competence, sigma-H controls genes involved in many physiological processes associated with the transition to stationary phase, including cytochrome biogenesis, generation of potential nutrient sources, transport, and cell wall metabolism.